Is fire “for the birds”? How two rare species influence fire management across the US - Stephens, Scott L; Kobziar, Leda N; Collins, Brandon M; Davis, Raymond; Fulé, Peter Z; Gaines, William; Ganey, Joseph; Guldin, James M; Hessburg, Paul F; Hiers, Kevin; Hoagland, Serra; Keane, John J; et al. (Frontiers in ecology and the environment, 2019)
The US Endangered Species Act has enabled species conservation but has differentially impacted fire management and rare bird conservation in the southern and western US. In the South, prescribed fire and restoration-based forest thinning are commonly used to conserve the endangered red-cockaded woodpecker (Picoides borealis; RCW), whereas in the West, land managers continue to suppress fire across the diverse habitats of the northern, Californian, and Mexican spotted owls (Strix occidentalis subspecies; SO). Although the habitat needs of the RCW and SO are not identical, substantial portions of both species’ ranges have historically been exposed to relatively frequent, low-to moderate-intensity fires. Active management with fire and thinning has benefited the RCW but proves challenging in the western US. We suggest the western US could benefit from the adoption of a similar innovative approach through policy, public–private partnerships, and complementarity of endangered species management with multiple objectives. These changes would likely balance long-term goals of SO conservation and enhance forest resilience.